2023
DOI: 10.1039/d3fd00049d
|View full text |Cite
|
Sign up to set email alerts
|

Ion adsorption and hydration forces: a comparison of crystalline mica vs. amorphous silica surfaces

Abstract: Hydration forces are ubiquitous in nature and technology. Yet, the characterization of interfacial hydration structures and their dependence on the nature of the substrate and the presence of ions have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…This independent behaviour excludes the force probed in 3D AFM with very sharp tips, as in our case, to be of electrostatic/van der Waals origin (the Debye length would decrease 100 times), and conrms previous observations obtained with similar AFM tips on crystalline materials for electrolyte concentrations below saturation. 51,52 The repulsive monotonic force contribution probed on the interfacial water of the L d phase might be better explained by considering a combination of relevant phenomena that occur upon phase transition: (i) the increased thermal thickness uctuations of the lipid bilayers; 16,53 and (ii) the soening of the bilayer in the L d phase. 48 It is difficult to determine which of the two is the dominant effect, nor can we exclude a combination of additional temperature dependent physical factors.…”
Section: Faraday Discussion Papermentioning
confidence: 99%
“…This independent behaviour excludes the force probed in 3D AFM with very sharp tips, as in our case, to be of electrostatic/van der Waals origin (the Debye length would decrease 100 times), and conrms previous observations obtained with similar AFM tips on crystalline materials for electrolyte concentrations below saturation. 51,52 The repulsive monotonic force contribution probed on the interfacial water of the L d phase might be better explained by considering a combination of relevant phenomena that occur upon phase transition: (i) the increased thermal thickness uctuations of the lipid bilayers; 16,53 and (ii) the soening of the bilayer in the L d phase. 48 It is difficult to determine which of the two is the dominant effect, nor can we exclude a combination of additional temperature dependent physical factors.…”
Section: Faraday Discussion Papermentioning
confidence: 99%
“…For example, hydration forces emerge at small particle separations and are associated with the removal of the interfacial solution structure between two colliding particles. This force is distinct from DLVO forces, and is often evaluated empirically as an exponential or double exponential term, with recent advances in AFM enabling direct measurements. Various studies reported that the hydration force reduces or even eliminates attachment of particles at high electrolyte concentrations, even if they can still form aggregates (sometimes leading to dynamic superlattice structures), particularly for smaller nanoparticles. Another example of non-DLVO forces–and a key protagonist in the current study–is the dipole–dipole interaction, which is not as ubiquitous as the hydration force, but rather specific to intrinsically polar crystal structures.…”
Section: Introductionmentioning
confidence: 90%